ONTOLOGI TERORISME DALAM PERSPEKTIF FILSAFAT EKSISTENSIALISME GABRIEL H. MARCEL - Reno Wikandaru (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2014)
Terrorism is one of the most terrible crimes. Various efforts have been conducted by the government, however, until now terrorism is still a serious issue. As a human behavior, the crime of terrorism is one thing that can be analized from various perspectives, as well as from the existentialism philosophy framework of Gabriel H. Marcel as described in this article. In relation to the analysis of terrorist behavior in Indonesia, it can be concluded that acts of terrorism, espe- cially those committed by suicide bombings, are ontologically behavioral parts of human chosen efforts to achieve